(untitled) (International Journal of Engineering and Computer Science, 2015)
The growing trend of blogging the experiences can provide good feedback for patients to take decision about the consumption of drugs. In order to extract information from blogs about various drugs and symptoms is a challenging task to data mining research community. Applying opinion mining concepts for drug review can lead to a useful platform to drug users to decide to go with particular drug or not. We propose an Apriori base model form retrieving information about various drugs and symptoms. The proposed model is tested on WebMD blog reviews which shown the good results.